Pengaruh Penggunaan Media Loose Part Terhadap Kemampuan Fisik Motorik Halus Pada Anak Usia Dini - Dikson Lenamah; Fridolina Lamak; Hagar Landjen; Yesri Liunokas; Sefanya Halla; Meri Natun; Fredericksen Victoranto Amseke (FKIP UNSULTRA, 2026)
This study is motivated by the importance of stimulation during the golden age to optimize the fine motor physical development of early childhood. The main focus of this research is the use of the most recent reference to explain the types of loose part materials—Daly and Beloglovsky (2022)—which are effective in stimulating hand–eye coordination and strengthening children’s small muscle development. The research was conducted at TK Kharisma Belo, Kupang City, with 15 children aged 5–6 years as research subjects. This study employed a quantitative research method. Data were collected using psychological scales, namely the Role Playing Scale and the Child Social Development Scale. The respondents consisted of 15 children selected using a total sampling technique at TK Kharisma Belo. Data analysis was carried out using simple linear regression analysis.The results of the study prove that variations in texture and the open-ended nature of loose part media (natural, recycled, and manufactured materials) have a positive and significant effect on the social development of children aged 5–6 years, contributing 96.9%. These findings support the theory that active engagement with concrete materials is crucial for children’s writing readiness and independence. The conclusion of this study states that loose part media is an effective and innovative strategy for developing fine motor physical skills in children at TK Kharisma Belo.